Building Integrated Photovoltaic is a Cost Effective and Environmental friendly Solution - M T ripathy; P K Sadhu (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Building integrated photovoltaic (BIPV) market is under developing stage with a relatively low number of installations worldwide. However, integrating photovoltaic technology into buildings is straight forward as no additional space is required and building materials are simply replaced by PV modules. Although BIPV is considered a promising technology, especially where land for large-scale PV plants is rare, several factors continue to constrain its wide-spread adoption BIPV thus promises to become an attractive alternative for both end users and for national policy makers. In this paper we analyse the investment of BIPV, benefits of BIPV power system and cost of BIPV power system. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7729